Cryptography : the key to digital security, how it works, and why it matters - Martin, Keith M. (W. W. Norton & Company, Inc., 2020)
"A nuts-and-bolts explainer book that explores what cryptography does, how it keeps us secure in cyberspace, and why it is so controversial. Though we may not see it, cryptography plays a critical role in our everyday lives, from the movies we stream and our Google searches to even opening our car doors with electronic key fobs. Broadly defined as a set of tools for establishing the basic elements of security in cyberspace, cryptography enables us to keep secrets and determine who we are talking to, as well as to detect changes to information. It underpins the security of mobile phone calls, card payments, web connections, internet messaging, and bitcoin transactions-in short, everything we do online. Yet, while we all rely crucially on encryption technology for our personal security, it is not without controversy. By preventing access to information in cyberspace, cryptography can hamper criminal investigations and obstruct national security efforts, and when deployed with ransomware it can even be used as a means of attacking computers. In this book, information security expert Keith Martin illuminates the many functions of cryptography and how we use it, leaving readers with a profound perspective on their own personal security"--